Convergence and synchronization in heterogeneous networks of smooth and piecewise smooth systems. (June 2015) - DeLellis, Pietro; di Bernardo, Mario; Liuzza, Davide
Abstract: This paper presents a framework for the study of convergence in networks where the nodes' dynamics may be both piecewise smooth and/or nonidentical. Sufficient conditions are derived for global convergence of all node trajectories towards the same bounded region in the synchronization error space. The analysis is based on the use of set-valued Lyapunov functions and bounds are derived on the minimum coupling strength required to make all nodes in the network converge towards each other. We also provide an estimate of the asymptotic bound on the mismatch between the node state trajectories. The analysis is performed both for linear and nonlinear coupling protocols. The theoretical analysis is extensively illustrated and validated via its application to a set of representative numerical examples.